Sensory Substitution and Augmentation 2018
DOI: 10.5871/bacad/9780197266441.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

Limits of the Classical Functionalist Perspective on Sensory Substitution

Abstract: The tongue display unit (TDU) is a sensory substitution device that translates visual images into electrotactile stimulation that is transmitted to the tongue and leads to new perceptual skills following training. Trained users, including blind individuals, become capable of orientation discrimination, motion detection, shape recognition and they can also successfully use the TDU to navigate in an environment, locate objects and avoid obstacles. Many studies and discussions have focused on the effects of train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Thus, the LOC likely processes more abstract object-form information regardless of the sensory modality of the input. This result suggests that the observed crossmodal recruitment of the visual cortex by sensory substitution devices could be due to the unravelling of preexisting computations through nonvisual inputs, present prior to using the SSD (e.g., Ptito et al, 2005;Striem-Amit et al, 2012; see also Ptito et al 2018, for a review). Beyond the LOC, typically nonauditory areas such as the left precentral sulcus and the right occipital-parietal sulcus also show differential activity following sensory substitution training (Striem-Amit et al, 2011).…”
Section: Key Results From Neuroimaging and Deprivation Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the LOC likely processes more abstract object-form information regardless of the sensory modality of the input. This result suggests that the observed crossmodal recruitment of the visual cortex by sensory substitution devices could be due to the unravelling of preexisting computations through nonvisual inputs, present prior to using the SSD (e.g., Ptito et al, 2005;Striem-Amit et al, 2012; see also Ptito et al 2018, for a review). Beyond the LOC, typically nonauditory areas such as the left precentral sulcus and the right occipital-parietal sulcus also show differential activity following sensory substitution training (Striem-Amit et al, 2011).…”
Section: Key Results From Neuroimaging and Deprivation Studiesmentioning
confidence: 94%
“…The mechanisms underlying this remarkable transformation of information from one sensory modality to another has been subject to much debate (Bach-y-Rita and Kercel, 2003;Keeley, 2002;Ptito et al, 2018). Several theories and models attempt to explain how the brain is able to exploit intact sensory modalities to perceive information that is normally conveyed through another modality.…”
Section: Dominance Deference and Multisensory Views Of Sensory Substitutionmentioning
confidence: 99%
“…However, the degree to which the use of a sensory substitution device involves visual processes varies from one person to another (Arnold et al, 2017). In parallel, brain-imaging studies have shown that the use and practice of visual-to-tactile (Ptito et al, 2005) and visual-to-auditory (e.g., Striem-Amit and Amedi, 2014) devices result in increased activation in blind people's visual cortex (for reviews, see Proulx et al, 2014;Ptito et al, 2018).…”
Section: Sensory Substitutionmentioning
confidence: 99%
“…One study directly compared activation longitudinally 20 and did not reveal increased activation, but a change in functional connectivity. This result suggests that the observed cross-modal recruitment of the visual cortex during the use of sensory substitution devices can be due to unmasking of existing computations through non-visual inputs already there prior to devices’ use 13 , 21 , 22 (see 23 for a review).…”
Section: Introductionmentioning
confidence: 99%